APLIKASI DISTRIBUSI DERET PANGKAT PADA BEBERAPA JENIS DISTRIBUSI KHUSUS - Talakua, Mozart Winston (PATTIMURA UNIVERSITY, 2012)
This research about the definition and theorem of power series distribution according to its analitycal characteristics. Then it discusse about the application to another distribution, anddiscusse about the relation between it, but it especially discusse about the application of power series distribution on some other special distribution, such as the negative logarithmdistribution, the divided logarithm distribution, and invers sinus distribution